Training and its role in improving employee productivity: A case study of the Zawiya branch of the Social Security Fund (Al-Farooq Journal of Sciences, 2026)
This study aims to identify training and its role in improving employee productivity by answering the research questions: To what extent do employees understand the concept of training? What is the role of training and the effectiveness of training programs in improving employee productivity at the Zawiya branch of the Social Security Fund? To answer these questions, a set of hypotheses was formulated to determine the relationship between the independent variables (employee understanding of the training concept, training practice, and the effectiveness of training programs) and the dependent variable (employee productivity). The study employed a descriptive methodology and analyzed data using statistical tests via the SPSS software package to obtain more accurate results. A questionnaire was designed and distributed to a simple random sample of (127) employees working at the Zawiya branch of the Social Security Fund. (120) questionnaires were returned and deemed valid for analysis, representing (94%). Through statistical analysis of the data, the study reached several conclusions, including a relationship between employee perception and productivity at the Social Security Fund branch. Most respondents indicated an understanding of the concept of training and a relationship between employee training and productivity. The results suggest that training improves performance levels and contributes to increased employee productivity. The results also showed a relationship between the efficiency of the training programs provided during the training courses and the increase in the productivity of workers. The results indicate that renewed, highly efficient and diverse training programs would contribute to increasing the productivity of workers. Through the analysis of the relationship via the correlation coefficient, it was shown that there is a positive (direct) relationship between training and improving the productivity of workers, meaning that the more the Social Security Fund pays attention to training workers, the more this improves the productivity of their employees. Based on the findings, the study recommends the continued provision of training courses for employees in all fields and efforts to promote a culture of knowledge that fosters understanding and appreciation of training and its role in improving employee performance and increasing productivity. It also emphasizes the importance of diversifying and updating training programs to enhance productivity, thereby creating greater performance differentiation and keeping pace with the introduction of new social security services in developed countries across all areas related to social security work.
Keywords: Training - Training Programs - Productivity